Comparison of Diagnostic Performance of B-Mode Ultrasonography and Shear Wave Elastography in Cervical Lymph Nodes. Issue 3 (September 2019) - Kang, Hye Jin; Seo, Mirinae; Sohn, Yu-Mee; Yun, Seong Jong; Min, Sun Young; You, Myung-Won; Yeon, Eung Koo
Abstract : Abstract: The purpose of this study was to compare the diagnostic performance of B-mode ultrasonography (US) and shear wave elastography (SWE) for differentiating benign from malignant cervical lymph nodes (LNs). This study evaluated 130 cervical LNs in 127 patients. On conventional B-mode US, short-axis and long-axis diameters, long-to-short-axis ratio, cortical morphology, border, and presence of necrosis or calcification were evaluated. Maximum elasticity value (Emax) was collected for SWE. The area under the receiver operator characteristic curve (AUC), sensitivity, and specificity of B-mode US features and SWE were compared. Final histopathologic results showed 89 benign and 41 metastatic LNs. Among the B-mode US features, cortical morphology had the highest AUC (0.884). When 54 kPa of Emax was applied as a cutoff value, the SWE showed significantly lower AUC than cortical morphology (0.734, P = 0.02). Both sensitivity and specificity for cortical morphology on B-mode US were higher than for Emax (80.5% vs 65.9%, P = 0.212 and 89.9% vs 76.4%, P = 0.026, respectively). Conventional B-mode US resulted in higher diagnostic yield than SWE in evaluating cervical LNs in our study. However, further studies on potential factors that may affect the SWE velocity are needed to validate the diagnostic value of SWE.